As relações étnico-raciais no manual do professor dos livros didáticos de História: análise da presença/ausência de uma pedagogia de concienctização contra o preconceito - Justino, Maria das Graças (2022)
The school is the place where the formation of citizens begins. Its role goes beyond its walls, because in its interior society is reflected through the students who are in it, and, many times, problems of all kinds are identified and worked pedagogically, in the search for paths and solutions. The present study aims to identify and analyze in the teacher's manuals of history textbooks if and how the ethnic-racial issue appears, in accordance with Law n°10.639/2003 and 11645/2008, in order to contribute to the discussion about prejudice at school and to raise awareness of society in favor of strengthening the identity, culture and history of Afro-descendant peoples throughout the history of our country. When looking at the manuals, we propose to analyze the editorial guidelines on ethnic-racial relations, realizing if they are present, what they delimit, how they approach, what kind of support they offer to teachers. Therefore, we aim to reflect on the guidelines given to the History teacher in order to combat discrimination. In the course of the research, we observed a reduced presence of the theme in the didactic materials under analysis and in this sense we prepared as a final product an orientation manual for teachers with a focus on the final years of Elementary School, but which can be adapted and implemented in other levels of education seeking contribute to a history teaching focused on the racial and cultural diversity present in Brazilian society. racial and cultural diversity present in Brazilian society. Within the scope of this research, we find relevant a foundation on racism in Brazilian society and in the school space to understand how public policies of reparation for black people are necessary for secular inequalities to be repaired. We dialogued with Lília Moritz Shwarcz, Kabengele Munanga, Sílvio de Almeida and Nilma Lino Gomes, among other authors, which provided us with subsidies to understand how ethnic-racial relations are addressed in the Teacher's Manual of History textbooks. In this sense, in the chapters of this research, we will carry out an analysis of the Teachers' Manuals in History textbooks to understand how the ethnic-racial issue is approached. We will seek to understand the role, advances and limits of official documents that deal with the teaching of this subject, and highlight the importance of devising strategies to combat racism in the school environment.